2011
DOI: 10.1073/pnas.1109435108
|View full text |Cite
|
Sign up to set email alerts
|

Motifs emerge from function in model gene regulatory networks

Abstract: Gene regulatory networks allow the control of gene expression patterns in living cells. The study of network topology has revealed that certain subgraphs of interactions or "motifs" appear at anomalously high frequencies. We ask here whether this phenomenon may emerge because of the functions carried out by these networks. Given a framework for describing regulatory interactions and dynamics, we consider in the space of all regulatory networks those that have prescribed functional capabilities. Markov Chain Mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 49 publications
4
102
0
Order By: Relevance
“…These results have been adopted in the systems biology community to the point that "feed-forward loops", "single-input module", and "bifan" are synonymous with motif. Subsequent work has linked the ubiquity of these motifs to convergent evolution driven by functional requirements (14,20). However, when using our evolutionary model, which accounts for events at the genomic level, it emerges that FFLs, SIMs, and bifans all occur within frequencies expected by neutral evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results have been adopted in the systems biology community to the point that "feed-forward loops", "single-input module", and "bifan" are synonymous with motif. Subsequent work has linked the ubiquity of these motifs to convergent evolution driven by functional requirements (14,20). However, when using our evolutionary model, which accounts for events at the genomic level, it emerges that FFLs, SIMs, and bifans all occur within frequencies expected by neutral evolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that when subjecting CRNs to the various neutral evolutionary forces and tracing their trajectory in time, many of these topological patterns may simply arise spontaneously due to the forces of mutation, recombination, gene duplication, and genetic drift (10, 12). These studies call into question arguments that were made in favor of adaptive explanations for the emergence and conservation of CRN properties (8,(13)(14)(15) and identify important parameters that may significantly affect the evolution of CRNs from a neutral perspective. Specifically (12), they highlighted the role that promoter length, binding-site size, and population size may play in forming certain topological patterns known as motifs.…”
mentioning
confidence: 99%
“…Several studies have made contributions towards identifying some design principles for oscillatory behaviour. Network motifs-recurrent patterns of interactions believed to form the building blocks of any complex network (Milo et al 2002;Yeger-Lotem et al 2004;Barabasi and Oltvai 2004;Alon 2007;Kim et al 2010)-have also been highlighted to some extent for oscillators (Ferrell et al 2011;Wagner 2005;Novak and Tyson 2008;Tsai et al 2008;Burda et al 2011;Lomnitz and Savageau 2014;Noman et al 2015;Semenov et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of transcriptional repressors to oscillating networks has been previously studied [45,46]. Negative feedback loops (analogous to gene expression suppression) have been associated with oscillating behavior in many biological systems [47], including E. coli [48], the Neurospora circadian oscillator [49], the cell cycle [50], the lac operon system [51] the p53-mdm2 system [52] and NF-kappa B translocation [53].…”
Section: Discussionmentioning
confidence: 99%